2011
DOI: 10.1093/jxb/err125
|View full text |Cite
|
Sign up to set email alerts
|

Starch biosynthesis in rice endosperm requires the presence of either starch synthase I or IIIa

Abstract: Starch synthase (SS) I and IIIa are the first and second largest components of total soluble SS activity, respectively, in developing japonica rice (Oryza sativa L.) endosperm. To elucidate the distinct and overlapping functions of these enzymes, double mutants were created by crossing the ss1 null mutant with the ss3a null mutant. In the F2 generation, two opaque seed types were found to have either the ss1ss1/SS3ass3a or the SS1ss1/ss3ass3a genotype. Phenotypic analyses revealed lower SS activity in the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 48 publications
11
80
0
1
Order By: Relevance
“…The synthesis of ADP-glucose by AGPase is the first committed step, and the rate-limiting step, for starch biosynthesis. Previous studies showed that mutant lines with high amylose contents often show elevated AGPase activities [10,11]. The results are shown in two different units, per microliter of extract and per endosperm, so the data is comparable to previous studies.…”
Section: Resultssupporting
confidence: 81%
“…The synthesis of ADP-glucose by AGPase is the first committed step, and the rate-limiting step, for starch biosynthesis. Previous studies showed that mutant lines with high amylose contents often show elevated AGPase activities [10,11]. The results are shown in two different units, per microliter of extract and per endosperm, so the data is comparable to previous studies.…”
Section: Resultssupporting
confidence: 81%
“…While the double ss1 ssIIIa null mutant is sterile, double mutants with a leaky ss1 and a null ssIIIa allele are fertile. These results further support the role of both SSI and SSIIIa in starch biosynthesis in rice endosperm and seed development [ 80 ].…”
Section: )supporting
confidence: 80%
“…ADP-glucose pyrophosphorylase (AGPase) activity was also higher in the ss3a mutant than in wild-type endosperm (Fujita et al , 2011. However, some isozymes affected the amylose content of rice seeds.…”
Section: Ssiiiamentioning
confidence: 99%